Pengaturan Jaminan Produk Halal di Indonesia - Amalia, Maya Rezka; Mariani, Mariani (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
MUI Halal Certificate is one of the requirements for obtaining permission to put a halal label on every product packaging from the government agency that has authority over it. The purpose of implementing the MUI halal certificate for all medicinal, food, cosmetic products and so on is to provide legal certainty over halal status, so that everyone can feel at ease when consuming it. Researchers utilize the type of empirical legal research that is qualitative in nature. This research is field research, strengthened by the existence of primary and secondary data sources, which are collected by researchers related to data using observation techniques. After the data is collected, it is processed through editing, categorization, and description processes. The definition contained in Law No. 33 of 2014 concerning Halah Guarantee Products is that halal products are products that have been declared halal in accordance with Islamic law. Which was then formulated in several applicable regulations including Law No. 11 of 2020 regarding Job Creation. It also contains information regarding the acceleration of regulations regarding JPH so that it can be carried out quickly and easily and becomes one of the positive implications of the ratification of Law No. 11 of 2020. Sertifikat Halal MUI adalah salah satu syarat untuk memperoleh izin untuk mencantumkan label halal di setiapkemasan produk dari lembaga pemerintah yang berkuasa atasnya. Tujuan Sertifikat halal MUI di segala produk obat-obatan, pangan, kosmetik dan lain sebagainya dilaksanakan untuk memberi kepastian hukum atas status kehalalan, agar bisa menenangkan batin bagi setiap orang saat mengonsumsinya.Peneliti memanfaatkan jenis penelitian hukum empiris yang sifatnya kualitatif. Penelitian ini yakni penelitian lapangan (field research), diperkuat adanya sumber data primer dan sekunder, yang dikumpulkan peneliti terkait data menggunakan teknik Observasi. Setelah data terkumpul lalu diolah melalui proses editing, kategorisasi, dan deskripsi. Pengertian yang terccantum dalam UU no 33 Tahun 2014 mengenai Produk Jaminan Halah adalah Produk halal adalah produk yang sudah dinyatakan kehalalannya selara akan syariat Islam. Yang kemudian dirumuskan dalam beberapa aturan yang berlaku ternasuk UU No 11 tahun 2020 terkait Cipta Kerja. Disana juga dimuat terkait percepatan aturan tentang JPH agar dapat terlaksana dengan cepat dan mudah dan menjadi salahh satu implikasi positif tentang pengesahan UU No 11 Tahun 2020 ini.